REVIEWS IN FORENSICANTHROPOLOGICAL IMPORTANCE OF STABLE ISOTOPEANALYSIS IN PROVENANCING UNKNOWN HUMAN REMAINS (Journal of Forensic Medicine & Toxicology, 2018)
Isotopes have been extensively utilized in diverse scientific fields like geology, ecology, hydrology, wildlife forensics, food industry, forensic anthropology and archaeology, geographical, pharmacological and   medical research for different purposes. Stable isotope analysis of the evidentiary material/s found in forensic and bioarchaeological contexts is gaining more and more importance these days around the globe. This  biogeochemical tool has been increasingly used in biological profiling of unknown human skeletal remains as to their geographic origin, migration patterns before or around death, dietary habits, pathological and   physiological stress status, drug origin, processing and its trafficking routes etc. It is comparatively a cost-effective, easy, quick and more objective method used for provenancing of osseous material in forensic  anthropological situations. Though this chemical forensic anthropological technique is still in its nascent phase and is to be accepted as a valid mean of establishing different components of identity, it is expected to have  boundless applications in forensic as well as allied disciplines of inquiry in near future. There is a dearth of such techniques and instrumentation to be used in Indian scenario for forensic purposes, though it has been widely used for scrutinizing the quality of food products (water, milk, and honey), drug smuggling and other commercial purposes. Present review paper has highlighted the current status of use of stable isotopic analyses for forensic anthropological purposes.
Keywords: Forensic anthropology; unknown human remains; provenancing; stable isotopes; origin and migration patterns; identification